(3GdRgQ GdfVQ aj fHC GdNVQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO abO JcQQ GdSDGd bOjekG hMOjKkG Yf GdNVQ UGMH ehSi hcfJ LeYJ ai Pdc eeG Ufa ajg HNUhU ef GdbOeGA CHh LYaQ Hf GdefGOi s
(3BNQgG (B:s
(3Je cJGH GdRgQ GdfVQ ai fHC GdNVQ , LeY TjNfG GdEeGe GHf MLQ GdcfGfi GdYSbdGfj s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B70 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B74 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B222 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs